Application of hybrid SiO2‐coated CdTe nanocrystals for sensitive sensing of Cu2+ and Ag+ ions. (20th February 2013) - Cao, Yongqiang; Zhang, Aiyu; Ma, Qian; Liu, Ning; Yang, Ping
ABSTRACT: A new ion sensor based on hybrid SiO2 ‐coated CdTe nanocrystals (NCs) was prepared and applied for sensitive sensing of Cu 2+ and Ag + for the selective quenching of photoluminescence (PL) of NCs in the presence of ions. As shown by ion detection experiments conducted in pure water rather than buffer solution, PL responses of NCs were linearly proportional to concentrations of Cu 2+ and Ag + ions < 3 and 7 uM, respectively. Much lower detection limits of 42.37 nM for Cu 2+ and 39.40 nM for Ag + were also observed. In addition, the NC quenching mechanism was discussed in terms of the characterization of static and transient optical spectra. The transfer and trapping of photoinduced charges in NCs by surface energy levels of CuS and Ag2 S clusters as well as surface defects generated by the exchange of Cu 2+ and Ag + ions with Cd 2+ ion in NCs, resulted in PL quenching and other optical spectra changes, including steady‐state absorption and transient PL spectra. It is our hope that these results will be helpful in the future preparation of new ion sensors. Copyright © 2012 John Wiley & Sons, Ltd.